Development and Validation of Chemometrics-Assisted Green UPLC-MS/MS Bioanalytical Method for Simultaneous Estimation of Capecitabine and Lapatinib in Rat Plasma. (27th July 2021) - Alrobaian, Majed; Panda, Sagar Suman; Almalki, Waleed H; Afzal, Obaid; Kazmi, Imran; Alossaimi, Manal A; Al-Abbasi, Fahad A; Katouah, Hanadi A; Rub, Rehan A; Kumar, B V V Ravi; Rahman, Mahfoozur; Beg, Sarwar
Abstract: A chemometrics-oriented green ultra-performance liquid chromatography-mass spectrometry/mass spectrometry method was developed and validated for the first-time simultaneous estimation of capecitabine (CAP) and lapatinib (LPB) along with imatinib (as internal standard (IS)) in rat plasma. Analytes were extracted using ethyl acetate as the liquid–liquid extraction media. In the pre-development phase, principles of analytical eco-scale were used to confirm method greenness. Subsequently, vital method variables, influencing method robustness and performance, were optimized using a chemometrics-based quality-by-design approach. Chromatography was achieved on a BEH C18 (100 × 2.1 mm, 1.7 μm) using isocratic flow (0.5 mL.min −1 ) of mobile phase acetonitrile (0.1% formic acid):0.002 M ammonium acetate in water as the mobile phase. The mass spectrometric detections were carried out in multiple reaction monitoring modes with precursor-to-product ion transitions with m/z 360.037 → 244.076 for CAP, m/z 581.431 → 365.047 LPB and m/z 494.526 → 394.141 for IS. The bioanalytical method validation studies were performed, ensuring regulatory compliance. Linearity ( r 2 > 0.99) over analyte concentrations ranging from 5 and 40 ng.mL −1 was observed, while acceptable values were obtained for all other validation parameters. In a nutshell, a robust and green bioanalytical method was developed and applied for the simultaneous estimation of two anticancer agents from rat plasma.